THE ANALYSIS OF BAGAN APUNG THE MOORING AT PELABUHAN PERIKANAN SAMUDERA BUNGUS WEST SUMATERA PROVINCE - Tengku Malinda; Eni Yulinda; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was about analysis Bagan Apung, was conducted on January 2015 at Pelabuhan Perikanan Samudera Bungus West Sumatera Province. The purpose of this analysis was to find out the big invesment, the feasibility investment and to find out the analysis sensitivity of business Bagan Apung. This research used by survey method with respondents were selected through purposive sampling. The purposive sampling was the fisherman Bagan Apung with ship on 21 GT and 30 GT. The result of this research showed that the investment of the Bagan Apung 21 GT was Rp 600.710.600,-, and the Bagan Apung 30 GT was Rp 740.993.000,-. Based investmen criteria the bagan apung 21 GT, the value of NPV was Rp 975.862.431,-, the value of BCR 1.21, IRR was 59,78%. And the Bagan Apung 30 GT the value of NPV was Rp 790.484.279,-, the value of BCR 1.15, IRR was 54,67%. The analysis of sensitivity bagan apung 21 GT operating cost incrused 10% and fixed production NPV amount Rp 511.763.174,-, BCR was 0.997 and IRR was 44,47%. And Bagan Apung 30 GT NPV amount Rp 250.936.156,-, BCR was 0.996, and the value of IRR 21%. The decline production 10% and fixed cost Bagan Apung 21 GT NPV amount Rp 414.176.931,-, BCR amount 1 and IRR was 41%. And Bagan Apung 30 GT NPV amount Rp 171.887.729, BCR amount 1.03 and IRR was 20.02%.Keyword: Bagan Apung, Investment, Analysis Business, PPS Bungus